Immunohistochemical analysis of steroidogenic enzymes in ovarian‐type stroma of pancreatic mucinous cystic neoplasms: Comparative study of subepithelial stromal cells in intraductal papillary mucinous neoplasms of the pancreas. Issue 5 (6th April 2016) - Ishida, Kazuyuki; Sasano, Hironobu; Moriya, Takuya; Takahashi, Yayoi; Sugimoto, Ryo; Mue, Yoshiharu; Murakami, Keigo; Fujishima, Fumiyoshi; Nakamura, Yasuhiro; Morikawa, Takanori; Motoi, Fuyuhiko; Suzuki, Takashi; et al.
Abstract : Mucinous cystic neoplasms (MCNs) are generally defined as cyst‐forming epithelial neoplasms that arise in the pancreas and harbor characteristic ovarian‐type stroma beneath the epithelium. In this study, we compared the immunoreactivity of steroid‐related factors in these subepithelial stromal cells in MCNs to those in intraductal papillary mucinous neoplasms (IPMNs) to further characterize this unique MCN ovarian‐type stroma through evaluation of sex steroid biosynthesis. Twenty MCNs and twenty IPMNs were examined. Immunoreactivity of steroid hormone receptors, including estrogen receptor (ERα and ERβ), progesterone receptor (PR, PR‐A, and PR‐B), and androgen receptor (AR), was more frequently detected in MCN ovarian‐type stromal cells than in IPMN stromal cells ( P < 0.01). The H‐scores (mean ± SD) of steroidogenic factor (SF)‐1 were also significantly higher in MCNs (112.3 ± 33.1) than in IPMNs (0.9 ± 1.2) ( P < 0.01). The steroidogenic enzymes cytochrome P450 cholesterol side‐chain cleavage enzyme (P450scc), cytochrome P450 17 alpha‐hydroxylase (P450c17) and 3β‐hydroxysteroid dehydrogenase (3β‐HSD) showed immunoreactivity in 9/20 (45.0 %), 15/20 (75.0 %) and 13/20 (65.0 %), respectively, of ovarian‐type stroma from MCN cases. These results demonstrate that the ovarian‐type stroma of MCNs can express steroidogenic enzymes. Thus, the ovarian‐type stroma of MCNs can produce sex steroids that may also act on these cells.